IL-33 signaling is dispensable for the IL-10-induced enhancement of mast cell responses during food allergy - Krajewski, Dylan; Ranjitkar, Saurav; Jordan, Nathan; Schneider, Sallie S.; Mathias, Clinton B. (Frontiers in Immunology, 2025)
BackgroundThe IL-33/ST2 axis plays a pivotal role in the development of IgE-mediated mast cell (MC) responses during food allergy. We recently demonstrated that the pleiotropic cytokine, IL-10, not only exerts proinflammatory effects on IgE-mediated MC activation, but also promotes IL-33-induced MC responses. However, whether IL-33 is necessary for IL-10’s proinflammatory effects has not been examined.MethodsTo therefore determine the role of the IL-33/ST2 axis in this pathway, we assessed the effects of IL-10 on IgE-mediated MC activation and food allergy development in wild-type (WT) and ST2-/- mice.ResultsIL-10 stimulation significantly enhanced IL-33 gene expression, ST2 receptor expression, cytokine production, mMCP-1 secretion, and proliferation in IgE and antigen-activated bone marrow-derived MCs (BMMCs) from WT mice. ST2-/- BMMCs exhibited reduced cytokine secretion in response to IgE-dependent activation. However, IL-10 enhanced cytokine production, mMCP-1 secretion, and proliferation in these cells as well. To further assess the role of IL-10, food allergy was induced in WT and ST2-/- mice subjected to antibody-mediated IL-10 depletion. IL-10-depleted WT mice exhibited a significant attenuation in MC-mediated responses to OVA challenge. While ST2-/- mice also exhibited a profound suppression of MC responses, IL-10 depletion had no additional effects. However, ST2-/-/IL-10-/- mice exhibited further decreases in OVA-IgE and antigen-specific MC activation compared to ST2-/- mice.ConclusionOur data demonstrates that IL-10 can enhance MC responses in both WT and ST2-/- mice, further corroborating its proinflammatory effects on MCs and suggesting that they are not regulated by IL-33 signaling.